2021
DOI: 10.1007/s10803-021-05187-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Morbidity Among Individuals with Autistic Spectrum Disorder: A Matched Controlled Population-Based Study

Abstract: In this study we aimed to assess whether individuals with ASD are prone to higher infection rates, or to severe COVID-19 illness. Individuals with ASD and age-and gender-matched controlled counterparts (total n = 32,812) were assessed for COVID-19 infection rates and hospitalizations. Results indicated higher infection rates among individuals with ASD, with the largest effect among individuals aged 40-60 (OR = 2.05, 95%CI 1.33-3.15, p < .001), as well as higher odds for hospitalizations, evident primarily in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Schott et al [ 38 ] showed an increased risk of SARS-CoV-2 infection in patients with autism, especially in those who live in a residential facility, those who receive home services from outside caregivers, who need a lengthy hospitalization, and those with comorbidities. Krieger et al [ 39 ] showed an increased rate of infection and hospitalization in persons with autism, especially men between 40 to 60 years. Karpur et al [ 40 ] showed that persons with autism are nine times more likely to be hospitalized and six times more likely to have extended hospital stays than those without autism.…”
Section: Covid-19 and Mortality Rates In Children With Autismmentioning
confidence: 99%
“…Schott et al [ 38 ] showed an increased risk of SARS-CoV-2 infection in patients with autism, especially in those who live in a residential facility, those who receive home services from outside caregivers, who need a lengthy hospitalization, and those with comorbidities. Krieger et al [ 39 ] showed an increased rate of infection and hospitalization in persons with autism, especially men between 40 to 60 years. Karpur et al [ 40 ] showed that persons with autism are nine times more likely to be hospitalized and six times more likely to have extended hospital stays than those without autism.…”
Section: Covid-19 and Mortality Rates In Children With Autismmentioning
confidence: 99%
“…The original database was originally mined by the beginning of February 2021 (see Krieger, Erez et al, 2021, Krieger, Grossman-Giron et al, 2021. Vaccination data were obtained from the CHS database by the end of February 2021.…”
Section: Data Sourcementioning
confidence: 99%
“…The diagnosis of ASD was based on codes 299 and F84 of the ICD-9 and 10 (pervasive developmental disorders) including the following subtypes: infantile autism (current or active state), disintegrative psychosis, other specified early childhood psychosis, unspecified childhood psychosis, pervasive developmental disorder, childhood autism, atypical autism, Rett syndrome, Asperger's syndrome, other pervasive developmental disorders, and pervasive developmental disorder unspecified (Krieger, Erez et al, 2021;Rai et al, 2017, Krieger, Grossman-Giron et al, 2021. The ASD diagnoses were based on the registration of either a community psychiatrist or as documented on a discharge letter from a hospital.…”
Section: Study Population and Disease Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 was the leading cause of death among those with intellectual and developmental disabilities in 2020 (6). People with specific diagnoses associated with ID are particularly prone to increased risk of hospitalization and death, including those with Down syndrome, Autism, cerebral palsy, and fragile X syndrome (7)(8)(9)(10)(11). There are numerous reasons why people with ID are particularly vulnerable to experiencing severe COVID-19 illness and death (12).…”
Section: Introductionmentioning
confidence: 99%